Bia improved yams - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Researchers at the University of Nigeria have shown that the dormancy period of white yams (Dioscorea rotundata) can be broken by applying the growth regulator BIA (butyric indolic acid) to the tubers before planting. Farmers can thus schedule...